Syllinae (Polychaeta, Syllidae) from Australia. Part. 2. Genera Inermosyllis, Megasyllis n. gen., Opisthosyllis, and Trypanosyllis - San Martín, Guillermo; Hutchings, Pat; Aguado, María Teresa (Zootaxa, 2008)
Large collections of Australian Syllidae (Polychaeta) from the Australian Museum (Sydney) have been examined and identified, together with material from the Hamburgische Zoologische Museum der Universität (Hamburg, Germany), as well as some specimens from other museums. All known Australian species of the subfamily Syllinae belonging to Inermosyllis San Martín, 2003 (1 species), Megasyllis n. gen. (3 species), Opisthosyllis Langerhans, 1879 (5 species), and Trypanosyllis Claparède, 1864 (2 species), are described and figured. The Scanning Electron Microscope was used to illustrate relevant taxonomic characters and reproduction methods in these genera. Inermosyllis pseudohaploides is described as a new species. Megasyllis is described as a new genus, including M. corruscans (Haswell, 1885) and M. heterosetosa (Hartmann-Schöder, 1991) from Australia, and M. inflata (Marenzeller, 1879) from Japan and Australia; thespecies M. multiannulata (Aguado, San Martín & Nishi, in press) from Japan is also referred to this genus. The genus Inermosyllis is reported for the first time from Australia, as well as the species Opisthosyllis longicirrata Monro, 1939 and Trypanosyllis aeolis Langerhans, 1879.